Rebel power: why national movements compete, fight, and win - Krause, Peter (Cornell studies in security affairs, 2017)
Power, violence, and victory -- Why national movements compete, fight, and win -- The Palestinian national movement : the Sisyphean tragedy of fragmentation -- The Zionist movement : victory hanging in the balance -- The Algerian national movement : the long, bloody march to hegemony -- The Irish national movement : where you stand depends on where you sit -- The politics of national movements and the future of rebel power